KEKERABATAN GENETIK ANTAR JENIS KANTONG SEMAR (Nepenthes spp.) BERDASARKAN PENANDA RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - Rita Elfianis; Zulfahmi; Rowmaina (AGROISTA : Jurnal Agroteknologi, 2017)
Pitcher plants (Nepenthes spp.) are an important economically as ornamental and medicine plants. They have a high degree of morphological variation and after ambiguis to distinguish among picher plants. The objective of research was to observe the genetic relationship among pitcher plant based on RAPD markers. Nine pitcher plants were analyzed using five RAPD primers. The result of this study showed that five RAPD primers selected were generated total 60 DNA fragments ranging from 150-1.450 bp. Genetic distance among pitcher plants ranged from 0.105 [N. trichocarpa (NXT) vs N. mirabilis (MIR)] to 0.545 [N. ampularia hijau (AHI) vs N. ampularia peristom merah (APM). Based on the dendogram of UPGMA, pitcher plants divided into four clusters. First cluster was formed six pitcher plants, e.g. Nepenthes ampularia corong (ACO), Nepenthes mirabilis (MIR), Nepenthes x trichocarpa (NXT), Nepenthes ampularia batik (ABA), Nepenthes grasilis merah (GME), Nepenthes grasilis hijau (GHI). Second, third, and fourth clusters having only one species, namely Nepenthes ampularia hijau (AHI), Nepenthes ampularia panjang batik (APB), Nepenthes ampularia peristum merah (APM), respectively. The result of this investigation will help breeders for pitcher plants improvement program in future.